ChemInform Abstract: Practical Synthesis of ε‐Carotene. Issue 27 (18th June 2015) - Wu, Chunlei; Cao, Ruiwei; Song, Xiaohua; Lv, Chunlei; Ye, Weidong; Pi, Shiqing; Chen, Chaohui; Shen, Runpu
Abstract The developed route is supposed to be useful for a large‐scale preparation of the title compound.